2019
DOI: 10.21077/ijf.2019.66.2.82397-07
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of reef associated fishes in hook and line fishery at Mandapam, Gulf of Mannar, south-east coast of India

Abstract: Reef associated fishes landed by hooks and lines at Mandapam landing centre in Ramanathapuram District, Tamil Nadu for a period of four years from October 2008 to May 2012 were studied based on fortnightly samplings. The hook and line fishing is seasonal in Gulf of Mannar and lasts for six months annually from October - November to April - May, as this area remains rough during the rest of the year. The average annual landing of fish during the study period was 171 t with a peak of 295 t in 2008-09 and showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 1 publication
(2 reference statements)
4
6
1
Order By: Relevance
“…However, after 90 days in experiment 1, abalone juveniles with BS substrate showed a positive allometric growth pattern (b = 3.14), while abalone juveniles with PVC substrate continued to show isometric growth (b = 2.95) (Table 10). This isometric growth of abalone juveniles with PVC substrate (SL range = 22-38 mm, mean = 29.57 mm) is consistent with the study of Najmudeen (2015), which also reported isometric growth of abalone juveniles in the SL size range of 25-35 mm. Interestingly, in our study the abalone juveniles with BS substrate (SL range = 24-42 mm, mean = 32.06 mm) showed a positive allometric growth pattern.…”
Section: Effects Of Using Bamboo Substratesupporting
confidence: 91%
“…However, after 90 days in experiment 1, abalone juveniles with BS substrate showed a positive allometric growth pattern (b = 3.14), while abalone juveniles with PVC substrate continued to show isometric growth (b = 2.95) (Table 10). This isometric growth of abalone juveniles with PVC substrate (SL range = 22-38 mm, mean = 29.57 mm) is consistent with the study of Najmudeen (2015), which also reported isometric growth of abalone juveniles in the SL size range of 25-35 mm. Interestingly, in our study the abalone juveniles with BS substrate (SL range = 24-42 mm, mean = 32.06 mm) showed a positive allometric growth pattern.…”
Section: Effects Of Using Bamboo Substratesupporting
confidence: 91%
“…Varghese, Ranjith, and Joshi (2017) reported a total of 98 species of reef fishes and reported that 69 species from bottom-set gillnet landings at Pamban from GoM. Thus, the number of species recorded was found to vary with type of gears and comparatively lower number of species was recorded in experimental longline landings during the present study, which is in agreement with the study conducted by Venkataramani ( 2011) and Varghese and Gandhi (2019). Among the seven orders reported in the present study, Perciformes order dominated with families such as Carangidae, Lethrinidae, Lutjanidae, Haemulidae, and Nemipteridae, which is in line with the recent study on check list of fishes of the GoM ecosystem, Tamil Nadu, India (Joshi et al, 2016).…”
Section: Biodiversity Associated With Longline Catchessupporting
confidence: 91%
“…There were several attempts made by different researchers to document the species diversity along GoM (Abraham, Joshi, and Sriramachandra Murty, 2011;Joshi et al, 2016;Joshi, Zacharia, and Kanthan, 2012;Manisseri et al, 2012;Varghese, 2011;Varghese et al, 2011;Zacharia, Joshi, and Kandan, 2011;Zacharia and Kannan, 2012). The present investigation was the first attempt to produce systematic list of fish caught using experimental longlines with different sizes and shapes of hooks along the GoM, India.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations